2017
DOI: 10.2320/matertrans.m2017131
|View full text |Cite
|
Sign up to set email alerts
|

Ultimate Rolling Texture in Pure Aluminum Highly Deformed by Accumulative Roll Bonding: Taylor Orientation Formed beyond Grain Subdivision

Abstract: The texture evolution of an accumulative roll bonding (ARB) processed commercial purity aluminium with lubrication was measured by electron backscattering diffraction with a eld emission-type scanning electron microscope. As a result of texture analysis using orientation distribution function maps, the highest intensity texture component was found to be Taylor orientation after ARB 6 cycle. The result suggests that the deformation of ultra ne grains is similar to Taylor model, which occurs in not only high pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The Cu/A5052 DMLs were fabricated by the ARB process in this study, and ultrafine grains were formed via "grain subdivision 28) ", which is also observed in the ARB-processed single-phase material. 29) In general, ARB-processed materials do not show high work hardening ability since an ultrafine-grained microstructure is formed via grain subdivision. Thus, the usual uniform deformation due to the introduction of dislocations via plastic deformation is suppressed.…”
Section: Criteria For Kink Formationmentioning
confidence: 99%
“…The Cu/A5052 DMLs were fabricated by the ARB process in this study, and ultrafine grains were formed via "grain subdivision 28) ", which is also observed in the ARB-processed single-phase material. 29) In general, ARB-processed materials do not show high work hardening ability since an ultrafine-grained microstructure is formed via grain subdivision. Thus, the usual uniform deformation due to the introduction of dislocations via plastic deformation is suppressed.…”
Section: Criteria For Kink Formationmentioning
confidence: 99%